Deposition of Wafer‐Scale Single‐Component and Binary Nanocrystal Superlattice Thin Films Via Dip‐Coating. (27th March 2015) - Gaulding, E. Ashley; Diroll, Benjamin T.; Goodwin, E. D.; Vrtis, Zachary J.; Kagan, Cherie R.; Murray, Christopher B.
<x xml:space="preserve">Abstract</x> Single‐component and binary nanocrystal superlattices are assembled over wafer‐scale areas using the dip‐coating method. A series of measurements are performed to confirm superlattice assembly. This study demonstrates the versatility of dip‐coating in depositing a diverse set of nanocrystal materials and superlattice structures, while combining large‐area deposition with nanoscale control.